Quantization of a 4th-Order Wave Equation - Barci, Daniel Gustavo (1990)
The quantization of a scalar field obeying a fourth-order wave equation is described. Faster-than-light particles appearing in the process are treated as ghosts, with the wrong relation between spin and statistics. In this way, positive energy spectrum, as well as positive metric in Fock space are obtained. Finally, some implications of an interaction described by a Lagrangian symmetrized in the scalar fields are briefly discussed.